2019
DOI: 10.3389/fimmu.2019.02265
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Programming of Macrophages: Implications in the Pathogenesis of Granulomatous Disease

Abstract: Metabolic reprogramming is rapidly gaining appreciation in the etiology of immune cell dysfunction in a variety of diseases. Tuberculosis, schistosomiasis, and sarcoidosis represent an important class of diseases characterized by the formation of granulomas, where macrophages are causatively implicated in disease pathogenesis. Recent studies support the incidence of macrophage metabolic reprogramming in granulomas of both infectious and non-infectious origin. These publications identify the mechanistic target … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
69
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(69 citation statements)
references
References 245 publications
(321 reference statements)
0
69
0
Order By: Relevance
“…Linke and Wilson et al in their studies showed that activation of rapamycin (mTOR) complex 1 (mTORC1) in macrophages in mice leads to the progression and development of granulomas. It has also been shown in people with a progressive sarcoidosis (10,11).…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Linke and Wilson et al in their studies showed that activation of rapamycin (mTOR) complex 1 (mTORC1) in macrophages in mice leads to the progression and development of granulomas. It has also been shown in people with a progressive sarcoidosis (10,11).…”
Section: Introductionmentioning
confidence: 86%
“…Recently, a lot of attention has been paid to the role of T17 lymphocytes in the pathogenesis of sarcoidosis, a subgroup of CD4+ lymphocytes expressing IL-17A, which exhibit pro-inflammatory or anti-inflammatory properties in response to the local inflammatory milieu. It has been shown that in sarcoidosis granuloma macrophages express CCR20, causing the attraction of Tx17, and the expression of IL-23 causes a significant increase in the concentration of IL-17A (11,12). The ratio between Th17 and Treg cells probably determines the development and clinical course of sarcoidosis and can serve as a prognostic marker.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, IFNc-activated M1 macrophages efficiently channel internalized glucose into aerobic (or anaerobic) glycolysis and the pentose phosphate pathway for ATP and NADPH production, which in turn is required for production of NADPH oxidase 2-driven ROS. 15 Glycolytically derived pyruvate is still catabolized in the mitochondria, but in an impaired tricarboxylic acid cycle in which flux through isocitrate dehydrogenase and succinate dehydrogenase is blocked, leading to citrate/ isocitrate and succinate accumulation, and increased mitochondrial ROS via reverse electron transport. Citrate accumulation drives the synthesis of fatty acids as well as the antimicrobial metabolite, itaconate, while increased succinate levels stabilize HIF-1a, promoting the transcription of glycolytic enzymes and inflammatory cytokines (i.e.…”
Section: Host Central Carbon Metabolismmentioning
confidence: 99%
“…75 This is in contrast to the situation for many other intracellular bacterial pathogens where increased autophagy results in their more efficient delivery to and degradation within the lysosome. 15,76 How AMPK is activated in Leishmania-infected macrophages remains unclear. Leishmania infection can lead to the efflux of ATP, 77 which would alter intracellular pools of AMP/adenosine diphosphate/ATP and potentially activate AMPK in the host cell.…”
Section: Ampk Signaling Also Modulates Leishmania Growthmentioning
confidence: 99%
“…Two of the four patients had significant improvements [ 24 ]. In the same vein, as activated macrophages are major players [ 25 , 26 ], McClain Caldwell et al hypothesized that human MSCs may reprogram alveolar macrophages from patients with sarcoidosis, and therefore could reverse the disease. In fact, unselected BAL cells, mainly macrophages, from sarcoidosis patients cocultured with mesenchymal stromal cells from healthy adults showed a switch from a pro-inflammatory to an anti-inflammatory pattern.…”
mentioning
confidence: 99%